2017
DOI: 10.1186/s12961-017-0211-y
|View full text |Cite
|
Sign up to set email alerts
|

Situating mobile health: a qualitative study of mHealth expectations in the rural health district of Nouna, Burkina Faso

Abstract: BackgroundThe implementation of mobile health (mHealth) projects in low- and middle-income countries raises high and well-documented expectations among development agencies, policymakers and researchers. By contrast, the expectations of direct and indirect mHealth users are not often examined. In preparation for a proposed intervention in the Nouna Health District, in rural Burkina Faso, this study investigates the expected benefits, challenges and limitations associated with mHealth, approaching these expecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 64 publications
(60 reference statements)
8
47
0
Order By: Relevance
“…Interrupted eye contact and passive involvement especially with illiterate and older women impeded trust building and effective engagement. On the other hand, assessment of the mobile santé Nouna intervention in rural Burkina Faso showed expectations of improved relationships between the health facility and the community with mHealth as an intermediary [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interrupted eye contact and passive involvement especially with illiterate and older women impeded trust building and effective engagement. On the other hand, assessment of the mobile santé Nouna intervention in rural Burkina Faso showed expectations of improved relationships between the health facility and the community with mHealth as an intermediary [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is especially interesting for LMICs, as mobile phone usage outperforms other communication infrastructure usage [ 98 ]. In total, 70% of the 7.4 billion users of cellular phones reside in LMICs, and especially in sub-Saharan Africa, mHealth had a rapid expansion, making this approach hugely promising [ 20 , 99 , 100 ]. The response to Ebola PoC in the last epidemic might serve as an example, as it was very fast as a result of the effective surveillance systems in place.…”
Section: The Usagementioning
confidence: 99%
“…This is starting to change as mHealth is more utilized. In a review of 255 studies of mHealth applications, 93 studies fell into the realm of health monitoring and surveillance, the second largest group with 88 publications concerned themselves with raising health awareness [ 98 ]; another study found the most used context to be increased patient follow-up, as well as patient compliance [ 100 ].…”
Section: The Usagementioning
confidence: 99%
“…Other projects using health ICTs in low-income countries have encountered similar challenges. 16,19,28 It is also essential to study the economic context in order to understand variations in the intervention’s effects and their dependencies on contextual factors. 36 We believe it is imperative that mHealth projects invest in suitable premises and equipment (quality of Internet service, ventilation, air-conditioning, relay generator, etc) to mitigate technological hazards, and ensure regular maintenance to ensure the service is uninterrupted.…”
Section: Discussionmentioning
confidence: 99%
“…16,25-27 Often, studies have narrowed in on issues of acceptability and people’s capacity to use the technology, but without examining their complex health behaviors and the processes involved in adopting the technology. 28…”
Section: Introductionmentioning
confidence: 99%